Synthesis, characterization and evaluation of polyacrylamide graft starch/clay nanocomposite hydrogel system for enhanced oil recovery - Rituraj Singh (KeAi Communications Co., Ltd., 2017)
Abstract In this paper the suitability of a graft polymer nanocomposite hydrogel system for enhanced oil recovery was examined using polyacrylamide graft starch/clay nanocomposite (a laboratory synthesized product) and chromium (III) acetate (crosslinker). X-ray diffraction analysis, Fourier transform infrared spectrometry analysis, field-emission scanning electron microscopy and transmission electron microscopy were carried out to reveal the laboratory synthesized product as a nanocomposite. The effects of various parameters like salt concentration, pH, temperature, polymer concentration and crosslinker concentration on the properties of the developed gel system were systematically evaluated. The thermal stability of the nanocomposite gel and the conventional gel system were also determined by thermogravimetric analysis. The graft polymer nanocomposite gel system exhibited acceptable gel strength, gelation time and gel stability compared with the conventional gel system. The nanocomposite gels prepared using a low crosslinker concentration showed higher gel strength and required longer gelation time than the conventional gel which is more desirable properties for the effective placement of gel during enhanced oil recovery operations. In addition, sand pack flooding experiments show that the graft polymer nanocomposite gels had better plugging capacity than the conventional gel systems under reservoir conditions. Hence, this gel system may be suitable in the water shutoff treatments required for enhanced oil recovery from oilfields.